Nursing interventions for people with type 1 diabetes and frequent hypoglycaemia. (2nd November 2021) - Kelly, Bethany
Abstract : Type 1 diabetes is a lifelong condition which affects all age ranges, for reasons unknown, and the UK has one of the highest incidences of this complex condition in the world. Type 1 diabetes is caused by autoimmune damage to the insulin-producing β-cells found in the pancreatic islet cells, leading to severe insulin deficiency. People with diabetes need to achieve a target glyosylated haemoglobin level to avoid macro- and microvascular complications, but there is the associated risk of hypoglycaemic events. These can vary in severity and consequences but will likely always cause worry for the person living with diabetes. There are many risk factors and reasons to be explored when looking at hypoglycaemia. This case study explores the nursing interventions that can be safely worked through and prioritised, within the community setting, to allow people with diabetes to be safe from severe hypoglycaemia, thus improving their quality of life and safety, as well as reducing costs for the NHS.